Hands-on Kubernetes on Azure : run your applications securely and at scale on the most widely adopted orchestration platform - Gopalakrishnan, Shivakumar; Lenz, Gunther (Packt Publishing, 2019)
This book will help readers to Deploy web applications securely in Microsoft Azure with docker container and having the need for clustering services to achieve high availability, dynamic scalability, and to monitor applications.